2010
DOI: 10.1111/j.1476-5381.2009.00520.x
|View full text |Cite
|
Sign up to set email alerts
|

Transient supersensitivity to α‐adrenoceptor agonists, and distinct hyper‐reactivity to vasopressin and angiotensin II after denervation of rat tail artery

Abstract: Background and purpose: Vascular 'denervation' hyper-reactivity has generally been investigated 1-2 weeks after administration of chemicals that temporarily prevent transmitter release, but do not necessarily inactivate the neuronal noradrenaline transporters (NETs). We have investigated the reactivity of rat tail arteries over longer periods after removing the terminals by surgical denervation. Experimental approach: Two and 7 weeks after denervation, myography was used to assess contractions of isolated arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 27 publications
(61 reference statements)
0
24
1
Order By: Relevance
“…Interestingly, some studies have challenged the concept of α-AR hypersensitivity by reporting no change in pressor response to norepinephrine in rats with complete cervical SCI (216,268), suggesting that apparent enhanced sympathetic response may be caused by periodic episodes of SPN hyperactivity rather than denervation-related hypersensitivity. Other studies have otherwise shown that arterial and venous blood vessels from rats with more chronic SCI markedly increase nerve-evoked constrictions (290,337), and the arterial vascular muscle is transiently supersensitive to α 1 and α 2 -AR agonists (338).…”
Section: Peripheral α-Adrenoceptor Hyperresponsivenessmentioning
confidence: 98%
“…Interestingly, some studies have challenged the concept of α-AR hypersensitivity by reporting no change in pressor response to norepinephrine in rats with complete cervical SCI (216,268), suggesting that apparent enhanced sympathetic response may be caused by periodic episodes of SPN hyperactivity rather than denervation-related hypersensitivity. Other studies have otherwise shown that arterial and venous blood vessels from rats with more chronic SCI markedly increase nerve-evoked constrictions (290,337), and the arterial vascular muscle is transiently supersensitive to α 1 and α 2 -AR agonists (338).…”
Section: Peripheral α-Adrenoceptor Hyperresponsivenessmentioning
confidence: 98%
“…As mentioned above, this could also be associated with a-MPT central effects. More importantly, HR maintenance could be due to opposing responses of the parasympathetic nervous system to reduced sympathetic activity (Dickson et al, 1981;Levy, 1984;Lacroix et al, 1990), in addition to potential cardiovascular supersensitivity to catecholamines that may occur immediately after a-MPT administration (Brus et al, 1970;Tripovic et al, 2010). In contrast, decreased HR upon DEX administration is probably a reflex central response to the elevated blood pressure.…”
Section: Discussionmentioning
confidence: 93%
“…Nevertheless, in the present study, vascular expression of α 1 -ARs did not change after PSL, and was similar in patients with CRPS type II and controls. Loss of neuronal noradrenaline transporters or other changes (e.g., in gap-junction proteins, angiotensin II receptor expression or intracellular signalling to contractile stimuli) may contribute to denervation supersensitivity [53].…”
Section: Discussionmentioning
confidence: 99%